2015
DOI: 10.1111/1475-6773.12307
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Technology Adoption in the Emergency Department

Abstract: Objective. To describe the trend in health information technology (IT) systems adoption in hospital emergency departments (EDs) and its effect on ED efficiency and resource use. Data Sources. 2007-2010 National Hospital Ambulatory Medical Care Survey -ED Component. Study Design. We assessed changes in the percent of visits to EDs with health IT capability and the estimated effect on waiting time to see a provider, visit length, and resource use. Principal Findings. The percent of ED visits that took place in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…Monitoring and evaluation of the emergency performance are the most important processes of this department. Developing the Quantitative Standards and specify the range of valid and meaningful indicators for any treatment in an emergency is the most important activity of this main process [23][24][25][26][27][28]. Today, emergencies faced with a large volume of patients and health IT has a key role in the management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring and evaluation of the emergency performance are the most important processes of this department. Developing the Quantitative Standards and specify the range of valid and meaningful indicators for any treatment in an emergency is the most important activity of this main process [23][24][25][26][27][28]. Today, emergencies faced with a large volume of patients and health IT has a key role in the management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus on actual usage at the point of care, in this case an ED encounter, removes the limitations posed by self-reported usage or use of organizational adoption as a proxy for actual usage. It is worth noting that several HIE studies which measure actual system usage have found positive effects [33][34][35], whereas those that look at organizational level adoption only, have not [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The infusion of health information technologies in ED environments is driven by the need to facilitate communication, promote ease of information flow and workflow and enhance decision making and patient safety (Kane and Luz 2015). It has been reported that health information technologies (HIT) capabilities lead to improvement in ED efficiency by reducing waiting times and improving turnaround times when ordering tests and medications during patient visits (Selck and Decker 2016).…”
Section: Is Implementation In the Edmentioning
confidence: 99%